Phosphorus requirement and nodulation of herbaceous and shrub legumes in low P soils of a Guinean Savanna in Nigeria - Sanginga, N.; Okogun, J.A.; Akobundu, I.O.; Kang, B.T. (Elsevier, 1996)
There is increasing interest to improve the N2 fixation and P use efficiency of herbaceous and shrub legumes currently being introduced in cereal-based cropping systems in the moist savanna zones of West Africa. Knowledge about N and P nutrition of these legumes can assist in adapting them to new areas where fertilizer use is not feasible by the smallholder farmers. Pot and field experiments were carried out to examine variation among potential herbaceous and shrub legumes for their ability to nodulate and to use P efficiently. These legumes were grown at two P levels (0 and 7 kg P ha−1) in soils collected from two fields with different cropping histories (compound and degraded fields) at Yamrat in the northern Guinea savanna of Nigeria. In the compound field, animal manure and household residues are applied annually whereas in the degraded field, cereals are grown continuously with minimal organic inputs. Significant differences in growth, P content and mycorrhizal infection rate occurred among the different legumes as affected by P and cropping history. Legumes grown in soil from the degraded field responded more to P application than those grown in soil from the compound field. Phosphorus responsive legume species e.g. Mucuna pruriens var. utilis (black seed) and Crotolaria ochroleuca, had a low mycorrhizal infection rate compared to lower P responsive species such as Lablab purpureus and Cajanus cajan. A significant relationship was found between mycorrhizal infection rate and plant growth but not with nodulation of these legumes. All legumes nodulated naturally and the proportion of N derived from atmospheric N2 ranged from 38% for Centrosema brasilianum to 90% for L. purpureus. Application of P increased the weight of nodules but did not improve the proportion of N2 fixation. This study showed that species such as L. purpureus has a high N2 fixing capability and can also adapt to low P soils conditions in the northern Guinea savanna of West Africa.